Early hCG addition to rFSH for ovarian stimulation in IVF provides better results and the cDNA copies of the hCG receptor may be an indicator of successful stimulation - Paraskevis Dimitris; Stefanidis Konstantinos; Kiapekou Erasmia; Arabatzi Helen; Kalofolias George; Anastasiadou Vasiliki; Sypsa Vana; Beloukas Apostolos; Loutradis Dimitris; Drakakis Peter; Makrigiannakis Antonis; Hatzakis Angelos; et al. (BMC, 2009)
Abstract A simple, safe and cost-effective treatment protocol in ovarian stimulation is of great importance in IVF practice, especially in the case of previous unsuccessful attempts. hCG has been used as a substitute of LH because of the degree of homology between the two hormones. The main aim of this prospective randomized study was to determine, for the first time, whether low dose hCG added to rFSH for ovarian stimulation could produce better results compared to the addition of rLH in women entering IVF-ET, especially in those women that had previous IVF failures. An additional aim was to find an indicator that would allow us to follow-up ovarian stimulation and, possibly, modify it in order to achieve a better IVF outcome; and that indicator may be the cDNA copies of the LH/hCG receptor. Group A patients (n = 58) were administered hCG and Group B rLH (n = 56) in addition to rFSH in the first days of ovarian stimulation. The number of follicles and oocytes and, most importantly, implantation and pregnancy rates were shown to be statistically significantly higher in the hCG group. This study has also determined, for the first time to our best knowledge, m-RNA for LH/hCG receptors in the lymphocytes of peripheral blood 40 h before ovum pick-up. cDNA levels of the hCG receptor after ovarian stimulation were significantly higher among women receiving hCG compared to those receiving LH. In addition, higher levels were encountered among women with pregnancy compared to those without, although this was not statistically significant due to the small number of pregnancies. It seems that hCG permits a highly effective and more stable occupancy of rLH/hCG receptors and gives more follicles and more oocytes. The determination of cDNA copies could be, in the future, a marker during ovulation induction protocols and of course a predictor for the outcome of ART in the special subgroup of patients with previous failures.